Geothermal produced fluids: Characteristics, treatment technologies, and management options. (October 2015) - Finster, Molly; Clark, Corrie; Schroeder, Jenna; Martino, Louis
Abstract: Geothermal power plants use geothermal fluids as a resource and create waste residuals as part of the power generation process. Both the geofluid resource and waste stream are considered produced fluids. The chemical and physical nature of produced fluids can have a major impact on the geothermal power industry and influence the feasibility of power development, exploration approaches, plant design, operating practices, and reuse/disposal of residuals. In general, produced fluids include anything that comes out of a geothermal field and must subsequently be managed on the surface. These fluids vary greatly, depending on the reservoir being harnessed, plant design, and life cycle stage in which the fluid exists, but generally include water and fluids used to drill wells, fluids used to stimulate wells in enhanced geothermal systems, and makeup and/or cooling water used during operation of a power plant. Additional geothermal-related produced fluids include many substances that are similar to waste streams from the oil and gas industry, such as scale, flash tank solids, precipitated solids from brine treatment, hydrogen sulfide, and cooling-tower-related waste. This review paper aims to provide baseline knowledge on specific technologies and technology areas associated with geothermal power production. Specifically, this research focused on management techniques related to fluids produced and used during the operational stage of a power plant, the vast majority of which are employed in the generation of electricity. The general characteristics of produced fluids are discussed. Constituents of interest that tend to drive the selection of treatment technologies are described, including total dissolved solids, noncondensable gases, scale, corrosion, silicon dioxide, metal sulfides, calcium carbonate, metals, and naturally occurring radioactive material. Management options for produced fluids that require additional treatment for these constituents are also discussed, including surface disposal; reuse/recycle; agricultural, industrial, and domestic uses; mineral extraction and recovery; and solid waste handling.